2022
DOI: 10.3389/fonc.2021.770325
|View full text |Cite
|
Sign up to set email alerts
|

m6A Methyltransferase METTL3 Promotes the Progression of Primary Acral Melanoma via Mediating TXNDC5 Methylation

Abstract: m6A modification is one of the most important post-transcriptional modifications in RNA and plays an important role in promoting translation or decay of RNAs. The role of m6A modifications has been highlighted by increasing evidence in various cancers, which, however, is rarely explored in acral melanoma. Here, we demonstrated that m6A level was highly elevated in acral melanoma tissues, along with the expression of METTL3, one of the most important m6A methyltransferase. Besides, higher expression of METTL3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…However, METTL3 is downregulated in breast cancer and associated with favorable survival in patients with triple-negative breast cancer (TNBC) 21 . METTL3 is upregulated in patients with acral melanoma and associated with a higher tumor stage 12 . Accordingly, we found that METTL3 was upregulated in melanoma samples and was associated with poor survival, acting as an independent prognostic factor in patients with melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, METTL3 is downregulated in breast cancer and associated with favorable survival in patients with triple-negative breast cancer (TNBC) 21 . METTL3 is upregulated in patients with acral melanoma and associated with a higher tumor stage 12 . Accordingly, we found that METTL3 was upregulated in melanoma samples and was associated with poor survival, acting as an independent prognostic factor in patients with melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…METTL3, as an m 6 A methyltransferase 3, is involved in carcinogenesis including melanoma 11 . METTL3 stimulates the proliferation of primary acral melanoma by m 6 A methylation of thioredoxin domain containing protein 5 (TXNDC5) 12 and contributes to PLX4032 resistance in melanoma by promoting epidermal growth factor receptor (EGFR) translation 13 . In addition, METTL3-mediated m 6 A modification of uridine-cytidine kinase 2 (UCK2) drives melanoma metastasis through Wnt/β-catenin signaling 14 , whereas depletion of METTL3 facilitates the response to anti-PD-1 treatment in melanoma 15 .…”
Section: Introductionmentioning
confidence: 99%
“…m6A methylation was first discovered in the 1970s and was the most common reversible epigenetic modification in mRNA [ 36 ]. As an important member of m6A methylation regulators, METTL3 is upregulated in osteosarcoma [ 37 ], melanoma [ 38 ], liver cancer [ 39 ], and colorectal cancer [ 40 ]. The present study suggested that m6A methylation level and the expression of METTL3 in GBM cells were significantly elevated than that in NHAs, which was consistent with previous studies [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 has oncological roles during AM progression by regulating the level of m6Amethylation containing thioredoxin domain 5 (TXNDC5). 85 METTL3 also regulates UM cell proliferation, migration and invasion by targeting and regulating the m6A mRNA methylation of c-Met. 86 Also in UM, ALKBH5 promotes metastasis by mediating FOXM1 mRNA demethylation, thereby increasing its expression and stability, and inducing epithelial-to-mesenchymal transition.…”
Section: M6a and Other Melanomasmentioning
confidence: 99%
“…The same m6A modification roles have been identified in other melanomas, such as acral melanoma (AM), ocular melanoma (OM), uveal (UM) and conjunctival melanoma (CM). METTL3 has oncological roles during AM progression by regulating the level of m6A‐methylation containing thioredoxin domain 5 (TXNDC5) 85 . METTL3 also regulates UM cell proliferation, migration and invasion by targeting and regulating the m6A mRNA methylation of c‐Met 86 .…”
Section: M6a and Skin Cancermentioning
confidence: 99%